2019
DOI: 10.1136/archdischild-2018-315487
|View full text |Cite
|
Sign up to set email alerts
|

Acute ataxia in paediatric emergency departments: a multicentre Italian study

Abstract: ObjectivesTo evaluate the causes and management of acute ataxia (AA) in the paediatric emergency setting and to identify clinical features predictive of an underlying clinically urgent neurological pathology (CUNP).Study designThis is a retrospective medical chart analysis of children (1–18 years) attending to 11 paediatric emergency departments (EDs) for AA in an 8-year period. A logistic regression model was applied to identify clinical risk factors for CUNP.Results509 patients (mean age 5.8 years) were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
0
12
0
8
Order By: Relevance
“…The diagnosis of acute cerebellitis rather than postinfectious cerebellar ataxia should be considered when MRI changes are noticeable in the cerebellar cortex and headache accompany ataxia. 2,3 Among the pathogens causing acute cerebellitis, varicella zoster, Epstein-Barr, herpes simplex-1, influenza-A, respiratory syncytial virus, rotavirus, cytomegalovirus, echovirus, coxsackie, mumps, measles, rubella, Mycoplasma pneumoniae and Streptococcus pneumonia are the most common. 2,3 To our knowledge, , SARS-CoV-2 has been associated to acute cerebellitis only in two children, although both featured by severe neurological presentations.…”
Section: At Hospital Admission a New Nasopharyngeal Swab Sample Tested Negative Elevated Anti-sars-mentioning
confidence: 99%
“…The diagnosis of acute cerebellitis rather than postinfectious cerebellar ataxia should be considered when MRI changes are noticeable in the cerebellar cortex and headache accompany ataxia. 2,3 Among the pathogens causing acute cerebellitis, varicella zoster, Epstein-Barr, herpes simplex-1, influenza-A, respiratory syncytial virus, rotavirus, cytomegalovirus, echovirus, coxsackie, mumps, measles, rubella, Mycoplasma pneumoniae and Streptococcus pneumonia are the most common. 2,3 To our knowledge, , SARS-CoV-2 has been associated to acute cerebellitis only in two children, although both featured by severe neurological presentations.…”
Section: At Hospital Admission a New Nasopharyngeal Swab Sample Tested Negative Elevated Anti-sars-mentioning
confidence: 99%
“…Ataksja nie stanowi częstego objawu w populacji pediatrycznej. W wieloośrodkowym, włoskim badaniu [1] spośród pacjentów w wieku 1-18 r.ż. zgłaszających się do pediatrycznej izby przyjęć ataksję zdiagnozowano zaledwie u 0,02% (508) dzieci.…”
Section: Wstępunclassified
“…Wśród pozostałych przyczyn ataksji ostrej wyróżnia się toksyczne działanie leków (przeciwpadaczkowych, przeciwnowotworowych, immunosupresyjnych i benzodiazepin) oraz zatrucia m.in. : alkoholem, rtęcią, talem, litem, toluenem [1].…”
Section: Ataksje Móżdżkowe O Przebiegu Ostrymunclassified
See 1 more Smart Citation
“…However, ACA is known to be the most common cause of childhood ataxia, accounting for 30% to 50% of childhood ataxia cases [5][6][7]. Garone et al [8] reported that the number of patients with acute ataxia as the chief complaint was 0.021% of all patients who visited the emergency room, and 33.6% of patients with acute ataxia were diagnosed with postinfectious ACA, which was the most common cause of acute ataxia.…”
Section: Introductionmentioning
confidence: 99%